Inovasi Pokja Bunda PAUD dalam Menyelenggarakan Sekolah Orang Tua Hebat (SOTH) dan BKB Emas (Bina Keluarga Balita Eliminasi Masalah Stunting) - Larasati, Dewi Citra; Lestari, Asih Widi; Bella, Natalia Priska (Universitas Tribhuwana Tunggadewi, 2025)
Currently, Indonesia is faced with a Double Burden of Nutrition or often called Double Burden, which means that at this time we are still working hard to overcome malnutrition problems such as underweight, stunting, and anemia, but at the same time also have to face the problem of overnutrition or obesity. Handling stunting due to lack of acute nutrition intake is said to be a national priority program that must be supported and also succeeded in the regions. As a partner of the government, TP PKK must be involved in handling stunting cases. PKK collaborates with related cross-sectors to tackle in Pandanwangi Village. This study aims to determine the Innovation of the PAUD Bunda Working Group and the factors that influence the Innovation of the PAUD Bunda Working Group in organizing great parent schools (SOTH). This research method uses qualitative methods. The data collection techniques used are interviews, observation, and documentation. The informant determination technique is purposive sampling, namely Bunda PAUD Pandanwangi Village, Head of POKJA Bunda PAUD Pandanwangi Village and SOTH school principal. The results of the researcher's research show that the Innovation of the PAUD Bunda Working Group in Organizing an Independent Great Parent School (SOTH) in Pandanwangi Village has launched several innovations, namely curriculum surgery, socialization laucing, making APE mandir, coordination with cross-sectors, independent costs with self-help community affairs, collaborating with universities related to the Great Parents School (SOTH). As for the supporting factors, namely the enthusiasm of the principal and support from SOTH participants, community service (ABDIMAS) by UNITRI lecturers and inhibiting factors, namely the absence of funds from Social Services, and obstacles from mothers so that they do not attend SOTH meetings. Saat ini Indonesia dihadapkan pada Beban Gizi Ganda atau sering disebut Double Burden, yang artinya pada saat ini kita masih terus bekerja keras mengatasi masalah Kekurangan Gizi seperti kurus, stunting, dan anemia, namun pada saat yang sama juga harus menghadapi masalah kelebihan gizi atau obesitas. Penanganan stunting karena kurangnya asupan gizi akut disebut merupakan program prioritas nasional yang harus didukung dan turut disukseskan didaerah. Sebagai mitra pemerintah, TP PKK harus terlibat dalam penanganan kasus stunting. PKK bekerjasama dengan lintas sektor terkait untuk menanggulangi di Kelurahan Pandanwangi. Penelitian ini memiliki tujuan untuk mengetahui Inovasi Pokja Bunda PAUD dan faktor-faktor yang mepengaruhi Inovasi Pokja Bunda PAUD dalam menyelenggarkan sekolah orang tua hebat (SOTH). Metode penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Teknik penentuan informan adalah purposive sampling yaitu Bunda PAUD Kelurahan Pandanwangi, ketua POKJA Bunda PAUD kelurahan Pandanwangi dan Kepala sekolah SOTH. Hasil penelitian peneliti menunjukan bahwa Inovasi Pokja Bunda PAUD Dalam Menyelenggarakan Sekolah Orang Tua Hebat (SOTH) dan BKB Emas di Kelurahan Pandanwangi telah meluncurkan beberapa inovasi yaitu adanya bedah kurikulum, launcing sosialisasi , membuat APE secara mandir, koordinasi dengan lintas sektor, biaya mandiri dengan urunan panguyuban swadaya, berkerjasama dengan perguruan tinggi terkait Sekolah Orang Tua Hebat (SOTH). Sedangkan untuk faktor pendukung yaitu adanya semangat dari kepala sekolah dan dukungan dari perserta SOTH, pengabdian masyarakat (ABDIMAS) oleh dosen-dosen UNITRI dan faktor penghambat yaitu tidak adanya dana dari Dinas Sosial, dan adanya kendala dari ibu ibu sehingga tidak hadir dalam pertemuan SOTH.